NEW OSCILLATION THEOREMS FOR SECOND ORDER NONLINEAR DIFFERENTIAL EQUATIONS USING THE INTEGRAL AVERAGING TECHNIQUE - Salhin, Embark Abdalla; Salma Din, Ummul Khair; Ahmad, Rokiah Rozita; Noorani, Mohd Salmi Md (المجلة العلمية لكلية التربية, 2023)
By considering auxiliary functions, some new oscillation conditions are established for the second order nonlinear forced differential equations. Examples are given to illustrate the main results